Overview of national strategies on noncommunicable disease and adolescent health in South-East Asia Region countries - J S Thakur; Neena Raina; Priya Karna; Preeti Singh; Gursimer Jeet; Nidhi Jaswal (International Journal of Noncommunicable Diseases, 2016)
Research shows that risk factors for noncommunicable diseases (NCDs) are associated with behaviors that either begin or are reinforced during adolescence. Yet, focus on this age group in national NCDs policies globally or regionally in South-East Asia Region (SEAR) has not been adequately addressed. This overview of strategies to prevent NCDs among adolescents in SEAR countries provides a benchmark against which policy response can be assessed and strengthened. We reviewed all publically available documented strategies issued by governments in the 11 SEAR member countries of the World Health Organization on NCDs, published between January 1, 2002, and December 31, 2015. NCDs are currently a policy priority in many of the countries with school-based campaigns on healthy lifestyles; alcohol and tobacco-free environment and public ban on advertisements glamorizing unhealthy food among others. However, major challenges such as lack of specific focus on adolescents, lack of recognition of all major risk factors in national policies/programs, weak surveillance, unavailability of age disintegrated data, inefficient program management, low community awareness, and absence of multistakeholder policies persist. Of the countries reviewed, only 54.5% (6/11) proposed a policy that addressed all four of the main NCD risk factors - alcohol and tobacco use, physical inactivity, and obesity. This review demonstrates the disconnection between NCDs, adolescent health, and national policies.